A Study of Developing an Environmental Attitude Scale for Primary School Students - Eyup Artvinli; Zulfiye Melis Demir (Journal of Education in Science, Environment and Health)
The aim of this research is to develop an instrument that measures environmental attitudes of third grade students. The study was completed in six stages: creating scale items, content validity study, item total and remaining item correlation study, determining item discrimination, determining construct validity study and examining the internal consistency reliability of Cronbach’s Alpha. In this research, quantitative research methods and techniques were used. According to the data obtained from exploratory factor analysis, scale came under three sub-factors as “Positive Environmental Behaviors”, “Environmental Knowledge and Awareness” and “Negative Environmental Behaviors”. As a result of the confirmatory factor analysis, it is determined that chi square/df, RMSEA value and the other statistical significance levels are consistent with the collected data. Cronbach’s Alpha coefficient was taken between 0.71-0.94 for sub-scales and 0.93 for the total scale. In the light of these data, it is concluded that the environmental attitude scale has the validity and reliability.